Activities system using auditory stimulation techniques to improve listening skills - Jiménez Torres, Karen Brisseth; Valle Villon, Julieth Nahomy (Machala: Universidad Técnica de Machala, 2024)
The teaching of English in Ecuador presents many challenges among which is the constant struggle of teachers to optimize the ability of listening in students. For this reason, this research focuses on the problems that hinder the development of this skill in second-grade students, parallel A of the OE School. Hence, we propose a system of activities through the use of auditory stimulation techniques, so that students can strengthen their listening skills in English classes. This research is oriented towards the quantitative paradigm with an experimental design because it is intended to examine the progress in strengthening the students' listening skills. In addition to testing the hypothesis proposed through the collection of statistical data and knowing the effects of applying the variables, through the use of the pedagogical test, previously adapted to the academic plan and applied to the 26 students in the classroom. The problems of the object of study were evidenced, such as the students do not identify the basic vocabulary in English when playing audio, the students are not interested in listening and repeating the pronunciation of the words, there being few ludic activities during the English classes, the teacher does not take into account the level of the students when planning the activities. Therefore, this system includes combined activities that seek to promote the development of listening skills, providing fun and confidence to the student to achieve a good result in English classes while putting into practice the teaching of the language.
La enseñanza de inglés en Ecuador presenta muchos desafíos entre los cuales se encuentra la constante lucha de los docentes por optimizar la habilidad de listening en los estudiantes. Es por eso, que la presente investigación se centra en los problemas que dificultan el desarrollo de esta habilidad en los estudiantes de segundo de básica, paralelo A de la Escuela OE. Es por ello que, planteamos un sistema de actividades mediante el uso de técnicas de estimulación auditiva, con la finalidad de que los estudiantes logren fortalecer sus habilidades de escucha en las clases de inglés. Esta investigación está orientada hacia el paradigma cuantitativo con un diseño experimental, debido a que se pretende examinar el avance en el fortalecimiento de la habilidad de listening de los estudiantes. Además de probar la hipótesis planteada mediante la recolección de datos estadísticos y conocer los efectos de la aplicación de las variables, a través del empleo de la prueba pedagógica, previamente adaptada al plan académico y aplicada a los 26 estudiantes del salón. Se evidenció las problemáticas del objeto de estudio, tales como: los alumnos no identifican el vocabulario básico en inglés al reproducir el audio, los alumnos no están interesados en escuchar y repetir la pronunciación de las palabras, hay pocas actividades lúdicas durante las clases de inglés, el profesor no tiene en cuenta el nivel de los alumnos a la hora de planificar las actividades. Por tanto, este sistema incluye actividades combinadas que buscan impulsar el desarrollo de la habilidad de listening, brindándole diversión y confianza al alumno para lograr un buen resultado en las clases de inglés mientras que pone en práctica la enseñanza del idioma.
Keywords: ACTIVITY SYSTEM; ENGLISH LANGUAGE; LISTENING; TEACHING